Estrategias metodológicas para mejorar el aprendizaje de la ortografía - Acurio Salguero, Maricela Nataly (2022)
The present investigation under the title, Methodological strategies to improve spelling in students, was developed based on the spelling flaws that the children of the institution have, being a very important factor in the teaching-learning process, for which it was proposed Develop methodological strategies for the improvement of spelling in students of Third Grade of Basic General Education of the Educational Unit "Emilio Terán", it should be noted that this proposal has been planned, structured and developed in order to solve the problem, in addition , the analysis of the information that sustained and theoretically supported the variables was required, beginning by determining the weaknesses and strengths of a certain group of students through a qualitative and quantitative approach, as well as using certain techniques such as: a pedagogical test, interview and survey. Once the research stages have been completed and after validating and applying the methodological strategies, it is concluded that it was possible to provide a support tool for the teacher, which allowed the development of comprehension skills on the use of spelling rules, which allowed to build an adequate orthographic culture by improving written sentences.